Effects of an emotional intelligence & mindsets intervention on preservice teachers’ organisational citizenship behaviour and work engagement - Zungu, T.P. (2022)
The constructs of emotional intelligence (EI) and mindsets have been independently studied. However, given the positive outcomes associated with these constructs, they could be employed in a complementary and pragmatic manner. Against this backdrop, this thesis developed and investigated an intervention based on EI and mindsets. The main objective was to test the effects of this intervention on preservice teachers’ (PSTs) EI, mindsets, organisational citizenship behaviour (OCB) and work engagement. A review of the literature demonstrated that even though EI and mindsets interventions are increasing in education contexts, there seems to be a lack of interventions focusing mainly on PSTs. PSTs are vulnerable, as they are still in the process of constructing their teaching identity whilst dealing with the academic demands. Consequently, there is a need for interventions aimed to provide PSTs with the necessary psychological tools needed to cope with the pressures of their field.